CAPITAL WITHOUT STATEHOOD: EMPIRICAL STUDIES IN STARAYA LADOGA, KASIMOV AND MYSHKIN - I. Y. Okunev; D. V. Basova (Vestnik MGIMO-Universiteta)
The article covers the concept of "capitaleness" and "geographical identity". Our research will make an attempt to analyze an institute of capitals at functional as well as symbolic levels. In that case capitals serve not only as a place to dispose the governmental bodies, but their functions include national representation to themselves and the environment. Capitals are the idealized image of nation and national history, a sort of nation in miniature. Interregional differentiation within a state through establishing and maintaining mental boundaries between center and periphery is the mechanism to detect the territories needing the support for preserving the compliance with national norms and, thereafter, maintaining stateness. Two major territorial bases of stateness are traditionally singled out: nation-building and threats to security or, in other words, mental boundaries marking of "Us" community and actualization of "Others". Contemporary political geography is turning to the study of the third mechanism - internal "Other". Two strategies are possible to prove that interregional differentiation is a mechanism of nation-building. Analysis of different discursive and institutional practices marginalizing regions would be logical. However such way leads us to the large number of cases differing from each other in the multitude of variables and, therefore, exclude generalization in the conclusions. Thereupon we consider it possible to address another strategy, such as the search for evidence that center is purposefully opposed to periphery and is given symbolic national and centrifugal functions as well as administrative ones. The existence of one dichotomic pole should confirm the existence of the opposite. There are three cases - of Staraya Ladoga, Myshkin and Kasimov - which interpret differently the peculiarities of geographical space. Besides, the authors give illustrative examples of the construction of the myth about "stolichnost" and describe the instruments of symbolic politics.